Kazakhstan Trade Report : Improving the Regulatory Framework for Non-Tariff Measures - World Bank (Washington, DC, 2015)
The main message of this report is that if Kazakhstan wants to take advantage of global integration and diversification opportunities, the government needs to improve its trade policy framework, its management, and its regulations. It is also finalizing accession to the World Trade Organization (WTO) while its trade strategy includes a number of free trade agreements to be negotiated. It is an active member of the Central Asia Region Economic Cooperation (CAREC). This report is composed of three policy notes that discuss how to improve the trade policy framework, management, and regulations: note one is on the trade policy framework and recommends joining the WTO on a tariff schedule that is more liberal than Russia’s; note two postulates that to benefit more fully from the WTO membership and future regional or bilateral agreements, the institutional framework for trade policy management will need a clearer strategic vision, better coordination within the government and with private sector, and enhanced human capacity; and note three suggests that for the private sector to benefit from global integration and diversification, the government should ease the burden of regulations that affect trade (non-tariff measures (NTMs)).